Consanguinity: A blessing or menace at population level?. (19th March 2019) - Bhinder, Munir Ahmad; Sadia, Haleema; Mahmood, Nasir; Qasim, Muhammad; Hussain, Zawar; Rashid, Muhammad Mudassar; Zahoor, Muhammad Yasir; Bhatti, Rashid; Shehzad, Wasim; Waryah, Ali Muhammad; Jahan, Shah
Abstract: Consanguinity has highly complex and multifaceted aspects with sociocultural as well as biological debates on its pros and cons. The biological upshot of consanguinity includes the increased homozygosity, which results in manifold increased risk of genetic disorders at family and population levels. On the other hand, in addition to social, cultural, political, and economic benefits, consanguineous marriages have biological advantages at the population level. The consequence of consanguineous marriages is an upsurge in the number of homozygous diseased individuals with fewer chances of mating and reduced chances of survival, therefore evolutionarily confining the transmission of disease alleles to future generations and encouraging its elimination from a population. Protective effects of consanguinity have also been observed in a few diseases in different populations. Although attractive for many reasons, nonconsanguineous marriages will cause risk alleles to spread throughout the population, making most individuals carriers, and ultimately will resume the production of recessive diseases in subsequent generations. Although consanguinity, from an evolutionary point of view, is beneficial at the population level, it increases the risk of diseases in the very next generation. Presently, there is no treatment for most of the genetic disorders; we cannot opt for consanguinity for long‐term benefits. Nonconsanguineous marriages are a better strategy by which we may delay disease manifestation for some generations until science offers a viable solution.